Beyond the great divide : globalization and the theory of international relations - Clark, Ian (1998)
Presents globalization as an opportunity to rethink the Great Divide and the analytical schemes which have been deployed to legitimize it. Argues that globalization is more significant for its erosion of the internal/external divide than for its erosion of state capacity. Suggests that such an analytical shift might have utility for rethinking related issues about the viability of state capacity in the normative, democratic and security spheres as well.